2020
DOI: 10.1186/s41824-020-00088-6
|View full text |Cite
|
Sign up to set email alerts
|

Not all that glitters is COVID! Differential diagnosis of FDG-avid interstitial lung disease in low-prevalence regions

Abstract: Coronavirus disease-19 (COVID-19) is only one of the many possible infectious and non-infectious diseases that may occur with similar imaging features in patients undergoing [18F]-fluorodeoxyglucose (18FDG) monitoring, particularly in the most fragile oncologic patients. We briefly summarise some key radiological elements of differential diagnosis of interstitial lung diseases which, in our opinion, could be extremely useful for physicians reporting 18FDG PET/CT scans, not only during the COVID-19 pandemic, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…It should be noted that pulmonary manifestations of COVID-19 in PET/CT are not specific. Increased 18 F-FDG uptake in the area of ground-glass opacities, the most remarkable imaging feature reported, could also be observed in a variety of diseases, especially for other pulmonary infections [ 37 , 38 ]. To identify specific 18 F-FDG PET imaging features of COVID-19, a recent study included 11 COVID+ patients and 11 COVID- subjects (8 bacterial pneumonia, 2 granulomatosis, and 1 lymphoma) and compared the differences between groups in imaging [ 39 ].…”
Section: Pet In the Covid-19 Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that pulmonary manifestations of COVID-19 in PET/CT are not specific. Increased 18 F-FDG uptake in the area of ground-glass opacities, the most remarkable imaging feature reported, could also be observed in a variety of diseases, especially for other pulmonary infections [ 37 , 38 ]. To identify specific 18 F-FDG PET imaging features of COVID-19, a recent study included 11 COVID+ patients and 11 COVID- subjects (8 bacterial pneumonia, 2 granulomatosis, and 1 lymphoma) and compared the differences between groups in imaging [ 39 ].…”
Section: Pet In the Covid-19 Detectionmentioning
confidence: 99%
“…However, limited data have been reported to demonstrate the differences of PET features between COVID-19 and other viral pneumonia. Subtle radiological features, such as pleural effusion, bronchiectasis, and bronchial wall-thickening, may help the differential diagnosis [ 37 ]. It was suggested that COVID-19 was more likely to have a peripheral distribution (80% vs. 57%), ground-glass opacity (91% vs. 68%), fine reticular opacity (56% vs. 22%), and vascular thickening (59% vs. 22%), but less likely to have a central + peripheral distribution (14% vs. 35%) and pleural effusion (4% vs. 39%) [ 40 ].…”
Section: Pet In the Covid-19 Detectionmentioning
confidence: 99%
See 1 more Smart Citation